Chronic Pancreatitis with Acinar–Ductal Metaplasia and Ductal Dysplasia in a Horse. Issue 2 (August 2015) - Leipig, M.; Abenthum, K.; Wollanke, B.; Czupalla, I.; Esposito, I.; Steiger, K.; Hermanns, W.; Herbach, N.
Summary: A 16-year-old Friesian gelding with relapsing colic was humanely destroyed during diagnostic laparotomy due to suspected abdominal neoplasia. On post-mortem examination, the pancreas appeared as a firm mass (20 × 8 × 8 cm). The cut surface had a lobular structure with multiple cavities. Histological examination revealed severe chronic fibrosing pancreatitis with acinar–ductal metaplasia and duct dysplasia, which was considered to be the cause of the recurrent colic. Formation of tubular complexes within a background of acinar–ductal metaplasia is similar to the regressive lesions detected in the human pancreas in the context of inflammation, duct obstruction, cystic fibrosis and neoplasia. Pancreatic acinar–ductal metaplasia and ductal dysplasia are considered to be preneoplastic conditions in man and in the mouse.